ANALYSIS OF CONTENT MARKETING, EWOM, AND BRAND IMAGE IN DRIVING CUSTOMER TRUST AND PURCHASE DECISION IN DIGITAL HEALTH CONSULTATION SERVICE - Novitasari, Syadela; Suhud, Usep; Berutu, Meta Bara (International Journal of Multidisciplinary Research and Literature, 2026)
This study aims to analyze the influence of Content Marketing, Electronic Word of Mouth (EWOM), and Brand Image on Customer Trust and Purchase Decision among consumers of Halodoc digital health consultation services. The research method employed was quantitative causal research. The research sample was obtained using a non-probability purposive sampling technique, consisting of 253 respondents domiciled in DKI Jakarta. Data were collected through a digital questionnaire and were processed using SPSS and AMOS software. The analytical technique used was Structural Equation Modelling (SEM). The results indicated that content marketing, EWOM, and brand image had a positive and significant effect on customer trust. Furthermore, content marketing, EWOM, and brand Image also has a positive and significant effect on purchase decision. The findings also showed that customer trust has a positive and significant effect on Purchase Decision. This study provides theoretical implications that support previous digital marketing research within the context of digital health services. The practical implication for digital health consultation service providers is the need to strengthen the foundation of consumer trust by delivering more transparent information regarding service quality, the credibility of medical professionals, and authentic user-generated testimonials.